(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The modern volleyball game was characterized by speed and numerous procedures, and the blocking wall talent requires the participant to be aware of the to-be-had data about the appropriate synchronization of the leap and impeding the attacking participant from accomplishing an excessive-precision ball hit or blocking off the ball, and that terrible timing and accurate synchronization of the leap via the blocking player cause the weak point "I’ve a crew defense." The study objective to perceive the mechanism of synchronization and the differences between the motion of the blockading wall player and the attacking participant and a few biochemical variables between two one-of-a-kind heights of the assault, and the researchers used the descriptive approach in a survey method to healthy it with the tactics and nature of the studies on a pattern of the Iraqi countrywide group gamers for the year (2019-2020) and the maximum vital conclusions that The participant on the wall of the blocker works to comply with the movement of the attacking player and does not start to thrust upward until after the attacker receives up, and all of that is a manner to outline the assault location and observe the ball with a time that varies in line with the type of attack and the peak of the hit ball.